Student Teachers’ Readiness for Instructional English in Primary Classrooms - Rifhani Handayani L; Rahmat Darmawan; A. Muhajir Nasir (Journal of English Language and Education, 2026)
This study examines student teachers’ readiness to use instructional English in primary classroom contexts. A quantitative survey design was employed involving 133 student teachers from a Primary School Teacher Education (PGSD) program at a public university in Indonesia. Readiness was conceptualized as a multidimensional construct encompassing knowledge, classroom language skills, self-confidence, and classroom interaction readiness. Data were collected using a self-developed questionnaire and analyzed using descriptive statistics. The results indicate a moderate level of readiness across all dimensions. Classroom Language Skills shows the highest mean score (M = 16.32, SD = 3.006), followed by Classroom Interaction Readiness (M = 13.62, SD = 2.492) and Self-Confidence (M = 12.95, SD = 2.820), while Knowledge of Instructional English records the lowest mean (M = 12.01, SD = 1.905). The findings reveal an imbalance in which performance-related competencies are more developed than conceptual understanding and confidence. This suggests that current ESP practices support functional language use but are less effective in fostering adaptive and confident instructional communication. Strengthening the integration of knowledge, practice, and reflective experience is therefore essential to better prepare student teachers to use English as a medium of instruction.